2012
DOI: 10.1242/jeb.068312
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned response to a magnetic anomaly in the Pekin duck (Anas platyrhynchos domestica) involves the trigeminal nerve

Abstract: SUMMARYThere have been recent calls to develop protocols that collect unambiguous measures of behaviour using automatic techniques in conditioning experiments on magnetic orientation. Here, we describe an automated technique for recording the behaviour of Pekin ducks in a conditioning test that allows them to express unrestricted searching behaviour. Pekin ducks were trained to find hidden food in one corner of a square arena below which was placed a magnetic coil that produced a local magnetic anomaly. The tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…This discrimination was reversibly abolished by local anaesthesia applied to the upper beak and irreversibly after bilateral sectioning of V1 nerves. Similar results were obtained in Pekin ducks (Anas platyrhynchos domestica; Freire et al, 2012). We have been able to show the ability of Eurasian reed warblers (Acrocephalus scirpaceus) to compensate for a 1,000 km eastward displacement during spring migra tion was critically dependent on information transmit ted via V1 (Kishkinev et al, 2013).…”
Section: Kishkinev Chernetsovsupporting
confidence: 83%
“…This discrimination was reversibly abolished by local anaesthesia applied to the upper beak and irreversibly after bilateral sectioning of V1 nerves. Similar results were obtained in Pekin ducks (Anas platyrhynchos domestica; Freire et al, 2012). We have been able to show the ability of Eurasian reed warblers (Acrocephalus scirpaceus) to compensate for a 1,000 km eastward displacement during spring migra tion was critically dependent on information transmit ted via V1 (Kishkinev et al, 2013).…”
Section: Kishkinev Chernetsovsupporting
confidence: 83%
“…that the magnetic field direction provides a landing direction indicator as suggested in the introduction. The fact that magnetoreception has recently been shown in mallards, strengthens this hypothesis [13,14]. …”
Section: Discussionmentioning
confidence: 81%
“…Previous successful magnetic conditioning studies with pigeons had trained the animals to discriminate magnetic anomalies, which consisted of both changes in magnetic intensity and inclination, and were generated either by magnetic coils or a group of bar magnets (Mora et al, 2004;Thalau et al, 2007;Freire et al, 2012). Studies with homing pigeons (Wilzeck et al, 2010) as well as two other bird species, the domestic chicken (Gallus gallus) (Freire et al, 2005) and zebra finch (Taeniopygia guttata) (Voss et al, 2007;Keary et al, 2009), conditioned the birds to a shift in the horizontal component of the magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the ability to discriminate the presence and absence of a magnetic anomaly with changes in intensity and inclination was abolished following the sectioning of this nerve in homing pigeons (Mora et al, 2004). Whilst a possible role of the trigeminal nerve during homing by pigeons in Italy at distances of up to 105 km has been dismissed (Gagliardo et al, 2006;Gagliardo et al, 2009), several recent studies have investigated the role of the ophthalmic branch of the trigeminal nerve in transmitting magnetic information to the brain in migratory and non-migratory birds such as European robins (Erithacus rubecula) (Heyers et al, 2010) and Pekin duck (Anas platyrhynchos domestica) (Freire et al, 2012) and its role in correcting for displacement during migration in, for example, reed warblers (Acrocephalus scirpaceus) (Kishkinev et al, 2013). Two recent studies by Wu and Dickman (Wu and Dickman, 2011;Wu and Dickman, 2012) have also shown involvement of pigeon trigeminal neurons in magnetoreception, as well as recorded neuronal responses in the pigeon's brainstem in response to changes in direction, intensity and polarity of the magnetic field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation